Цифровізація економіки та зайнятості в умовах руху України до ЄС - Семикіна, М. В.; Костишина, А.; Савеленко, Г. В; Semykina, M.; Kostyshyna, A.; Savelenko, H. (ЧНУ ім. Б. Хмельницького, 2022)
У статті розкрито зміст явища цифровізації економіки та його вплив на різні сфери суспільного життя, що дозволило виявити особливості цього процесу для економіки й зайнятості населення в умовах руху України до ЄС. Визначено сутність цифровізації зайнятості, її виклики, можливості, наслідки, зокрема в частині виникнення нових видів і форм зайнятості, серед яких динамічно розвивається цифрова зайнятість. Проаналізовано глобальні тенденції цифровізації економіки й зайнятості з акцентом на держави ЄС, що дало змогу обґрунтувати стратегічний орієнтир повоєнного відновлення України на засадах цифрової економіки. Запропоновано активізувати заходи стимулювання цифровізації зайнятості в комплексі реалізації державної ініціативи «Industry 4.0». З урахуванням завдань повоєнного відновлення України й успішного руху в напрямі євроінтеграції визначено невідкладні заходи щодо створення сприятливих умов для цифрових трансформацій у сфері зайнятості з акцентом на підтримку молоді: підготовка кадрів із достатніми цифровими компетенціями, створення організаційно-правового середовища для цифрової зайнятості, підтримка цифрового бізнесу та працевлаштування молоді як стратегічного капіталу українського майбутнього. Introduction. Digitalization of economy is one of the defining trends of civilizational development, which has a direct impact on the entire sphere of social life, in particular, the employment of population. The research of these processes, search for new opportunities and prospects for the development of the employment sector under the influence of digitalization of the economy may be significantly updated шn the conditions of Ukraine's movement towards the EU. Purpose. The purpose of the article is to determine the features of the processes of digitalization of the economy and employment and to substantiate the possibilities of supporting the digitalization of employment in Ukraine in the interests of active use of the state's intellectual and labor potential at the stage of European integration. Results. The article reveals the essence of the digitalization of the economy, which allowed to reveal the peculiarities of this process, which leads to the transformation of employment. The content of digitalization of employment, its challenges, opportunities and consequences are defined, in particular from the point of view of the emergence of new types and forms of employment (casual, remote, platform, micro-work, online volunteering, etc.), among which digital employment is dynamically developing. Attention is focused on the spread of digital employment among young people as the main progressive and knowledge-oriented social group. The global trends of digitalization of the economy and employment are analyzed with an emphasis on EU countries, which makes it possible to justify the strategic direction of the post-war recovery of Ukraine based on the digital economy. It is proposed to intensify stimulation of the digitalization of employment within the framework of the implementation of the state initiative "Industry 4.0" in the context of Ukraine's movement to the EU. Originality. There are urgent actions which have been defined to create favorable conditions for digital transformations in the employment sector due to the tasks of the post-war recovery of Ukraine and the successful movement towards European integration. The main idea is to support youths: personnel training with sufficient digital competences; creation of organizational and legal environment for digital employment; support of digital business and youths’ employment as a strategic capital of Ukraine's future. Conclusion. Digitalization of economy and employment should be considered as a strategic reference point for the post-war recovery of Ukraine and its successful movement towards the EU. The basis of this process should be the support of digital employment of the population, especially young people. The implementation of the developed proposals for the development of digital employment in Ukraine under the conditions of targeted state support can have a cumulative effect on the economy, increase the welfare of population and reduce the emigration of young people, accelerate the country's movement towards European integration.
Digitalization of economy and employment in the conditions of Ukraine's movement to the EU
Keywords: цифровізація економіки; цифрова зайнятість; дистанційна зайнятість; Industry 4.0; цифрова трансформація; цифровий бізнес; молодь; digitalization of the economy; digital employment; remote employment; Industry 4.0; digital transformation; digital business; youths